2012
DOI: 10.1007/s40145-012-0033-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Zr0.85Y0.15O1.925-La9.33Si6O26 composite electrolyte for application in SOFCs

Abstract: (LSO) have been synthesized by a modified coprecipitation method. X-ray diffraction, electron microscope, and complex impedance were adopted to investigate the phase component, microstructures, and conductivities, respectively. The results show that the average grain sizes of the composite powders and as-sintered pellets are less than 20 nm and 200 nm, respectively. The conductivity of the composite materials composed of 94 wt% YSZ and 6 wt% LSO is 0.215 S/cm at 700 ℃. The conductivity of the composite is thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…A single Debye-like peak was clearly observed at all temperatures, and it shifted gradually toward higher frequencies with increasing temperature, indicating that the relaxation rate for this process increases with increasing temperature. The peak frequency of Z 00 max and M 00 max showed slight mismatch, which were correlated with the movement of oxygen vacancies, indicating the localized movement of oxygen vacancies [64]. This confirms that the relaxation process is temperature dependent and follows a non-ideal Debye-type relaxation in the ceramic.…”
Section: Resultssupporting
confidence: 64%
“…A single Debye-like peak was clearly observed at all temperatures, and it shifted gradually toward higher frequencies with increasing temperature, indicating that the relaxation rate for this process increases with increasing temperature. The peak frequency of Z 00 max and M 00 max showed slight mismatch, which were correlated with the movement of oxygen vacancies, indicating the localized movement of oxygen vacancies [64]. This confirms that the relaxation process is temperature dependent and follows a non-ideal Debye-type relaxation in the ceramic.…”
Section: Resultssupporting
confidence: 64%
“…1), the contents of La 9.33 Si 6 O 26 phase increase with increasing the contents of SiO 2 , and this phase is the major phase when x = 1.0. Thus variation of dielectric constants in La 1.5 Sr 0.5 NiO 4 -xSiO 2 composite ceramics can be explained easily since the dielectric constant of La 9.33 Si 6 O 26 is only about 30 at room temperature [16]. While the variations of dielectric losses are more complicated, and further research is need.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the XRD patterns of the ceramics at room temperature. The single phase is found in the La 1.5 Sr 0.5 NiO 4 The reaction between La 1.5 Sr 0.5 NiO 4 and SiO 2 will affect the dielectric properties of the ceramics, since the dielectric constant of La 9.33 Si 6 O 26 phase is only about 30 at room temperature [16]. Figure 2 shows the microstructures of the La 1.5 Sr 0.5 NiO 4 -0.8SiO 2 powders and the thermal-etched surfaces of La 1.5 Sr 0.5 NiO 4 -xSiO 2 (x = 0.0, 0.8) ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…However, that value is still low to be used as IT-SOFC electrolyte. Chao-feng et al, reported that the mechanical properties of apatites were unstable, brittle, and hygroscopic 6 . These weaknesses made the apatite-based electrolytes to be unsuitable for IT-SOFC electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…The first way of generating process is by modifying the microstructure of metal oxide. The second way is the use of composite material which is an easier way compared to the first one 6 .…”
Section: Introductionmentioning
confidence: 99%